Still Thinking and Feeling: the location of emotion in the creative and learning experience (Part 2): Paper adapted from the Keynote presented on 5 July at the Design and Technology Association Education and International Research Conference 2007 University of Wolverhampton, Telford. - Spendlove, David (Design and Technology Education: An International Journal, 2008)
This paper, the second of two parts, continues a broad overview of new opportunities for considering the location of emotion within a creative, learning and product orientated design and technology experience. The paper builds upon the author’s previous work and considers the location of emotion in three fluid domains: Person, Process and Product. The paper argues that for truly creative, engaging learning experience, the location of emotion is central but, more importantly, understanding the relationship of emotion to our decisions making offers greater opportunities for our future creative development.